2008
DOI: 10.1258/td.2007.053390
|View full text |Cite
|
Sign up to set email alerts
|

Childhood seroprevalence of hepatitis a in the United Arab Emirates

Abstract: The seroprevalence of hepatitis A in Emirati children less than 12 years was 20.1% (95% CI 16.4-24.6%) in 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…These results also suggest the transition pattern of HAV from high to intermediate endemicity, probably for the whole of Tunisia, previously classified among countries with high endemicity [19]. Similar epidemiological changes, associated with improved living conditions, are now being observed in many developing countries from the MENA region, such as Algeria, Kuwait, Saudi Arabia, the Emirates and Egypt [13,14,[37][38][39][40] as well as others countries in Africa, Asia, Europe and Latin America [10-16, 34, 35, 41-48]. Since older patients are usually symptomatic, the higher occurrence of infection during adolescence and adulthood results in an increased number of symptomatic cases and may lead to serious outbreaks.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results also suggest the transition pattern of HAV from high to intermediate endemicity, probably for the whole of Tunisia, previously classified among countries with high endemicity [19]. Similar epidemiological changes, associated with improved living conditions, are now being observed in many developing countries from the MENA region, such as Algeria, Kuwait, Saudi Arabia, the Emirates and Egypt [13,14,[37][38][39][40] as well as others countries in Africa, Asia, Europe and Latin America [10-16, 34, 35, 41-48]. Since older patients are usually symptomatic, the higher occurrence of infection during adolescence and adulthood results in an increased number of symptomatic cases and may lead to serious outbreaks.…”
Section: Discussionsupporting
confidence: 79%
“…The infection occurs more frequently in populations of less economically-developed regions with little education and poor hygiene [6]. Due to improved socio-economic conditions, the epidemiological pattern of hepatitis A infection recently changed in many parts of the world, including Asia, Latin America, Eastern Europe and the Middle East [2,[7][8][9][10][11][12][13][14][15][16]. Although this represents a positive indicator for socio-economic development, it leads to possible outbreaks due to the accumulation of seronegative subjects [17,18] and increased morbidity rate as a result of the increased age of primary infection.…”
Section: Introductionmentioning
confidence: 99%
“…A study held among healthy Kuwaiti adults (applying for a new job and those recruited for military service), reported 71% of cases being not immune to HAV . Single studies were reported from the United Arab Emirates (UAE) , Algeria , Iraq and Morocco in children and young adults. These studies show again the rise in seroprevalence with age leaving younger age groups with higher susceptibility to HAV infection (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This evolving pattern of endemicity may lead to serious outbreaks and significant disease burden since older patients are usually symptomatic. This epidemiology shift has been noted in the surrounding middle-east countries like Saudi Arabia, Lebanon, Kuwait, Qatar, Emirates, Tunisia, and several other countries [Tufenkeji, 2000;Sacy et al, 2005;Letaief et al, 2005;Almuneef et al, 2006;Sharar et al, 2008;Alkhalidi et al, 2009;Bener et al, 2009;Memish et al, 2010].…”
Section: Introductionmentioning
confidence: 88%